Analisis Haid Dan Nifas Dalam Perspektif Tafsir Al-Kabir Mafatihul Ghaib - nurhikmh, meli nurhikmah; Badi’ah, Siti; Windari, Fitri (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2025)
Conceptual gaps in public understanding of Sharia provisions regarding menstruation and postpartum bleeding (nifas) remain a crucial issue affecting aspects of worship and women's reproductive health. Previous studies have tended to separate fiqh analysis and linguistic studies, so the integration between classical interpretations and contemporary medical perspectives has not been optimal. This condition demands a multidisciplinary approach that can produce a more applicable and contextual understanding of Islamic law in relation to the development of modern health science. This research uses a qualitative method with a literature study approach to examine in depth the concepts of menstruation and postpartum bleeding in Tafsir al-Kabir Mafatihul Ghaib by Fakhruddin Ar-Razi. An integrative approach that harmonizes classical interpretation with cutting-edge medical science becomes the main analytical framework in this research. The results of the study reveal that Ar-Razi views menstruation and postpartum bleeding not only as biological phenomena, but also as having complex dimensions of Sharia law. In his interpretation of QS. Al-Baqarah verse 222, the term “adza” is interpreted as “dirt” (impurity) which includes the meaning of najis syar’i (legal impurity) as well as biological disturbances. This interpretation is the basis for prohibiting sexual relations during menstruation, which is not only oriented towards ritual aspects, but also as an effort to protect women's reproductive health from medical risks. This approach reflects a unique synthesis between medical and fiqh perspectives, enriching the dimensions of Islamic law interpretation related to reproductive health. This research affirms the urgency of a multidisciplinary approach in contemporary fiqh studies, especially in the context of women's health and worship, in order to broaden the horizons of Islamic law and offer relevant solutions to the challenges of the times.